Effects of working in the studied profession during a Master’s degree Nursing course on self-assessment of vocational preparation of students G - Gotlib, Joanna; Synowiec, Joanna (Polish Journal of Public Health, 2013)
Introduction. According to the National Qualification Framework (binding in Poland since the academic year 2012/2013), the analysis of self-assessment of students shall be one of mandatory components of evaluation of outcomes of education.Aim. The aim of the study was to analyse the self-assess-ment of nursing students of WMU regarding their vocational preparation as well as to compare the self-assessment of students who have taken on employment in their profession and those who have not.Material and methods. A group of 573 nursing students of the Faculty of Health Science, WMU (74.4% of students); 39% of the first year students and 55% of the second year students; women: 96%. Group 1 (446 persons, 78%) comprised those ho were working as nurses; Group 2 (126 persons, 22%) included those who were not working as nurses. An anonymous, voluntary questionnaire developed by the authors, a personal-ized link to the questionnaire http://www.ankieter.pl/wypelnij/ankiete/id/5612/. A non-parametric statistical Mann-Whitney U test was used for statistical analysis (p